Cross training WOD bible : 555 workouts from beginner to ballistic - Selter, P., ....- ([s.l.] : Shredded Society, 2014)
Here is A Preview Of What the Cross Training WOD Bible contains: A comprehensive list of the health benefits of Cross Training In depth terminology to help you understand the abbreviations and lingo used 555 Cross Training WODs (workouts) And Much More! Here is A Preview of the 555 Workouts the Cross Training WOD Bible contains: Beginner workouts ‘The Girls' – benchmark workouts Heroes – benchmark workouts Bodyweight workouts Running based workouts Rowing based workouts Kettlebell workouts Olympic lifting workouts Strongman workouts Short ‘N' heavy workouts Minute by minute workouts Bi-element workouts Tri-element workouts Four or more workouts Hybrid workouts AMRAP workouts Epic endurance challenges – designed to obliterate even the toughest endurance athletes There really is something for everybody in here!
Keywords: Krachttraining